LOS JUEGOS DE INICIACIÓN A LA CANTIDAD PARA EL DESARROLLO DEL ÁMBITO RELACIÓN LÓGICO MATEMÁTICO EN LOS ESTUDIANTES DE PRIMERO DE EDUCACIÓN BÁSICA PARALELO “B” DE LA UNIDAD EDUCATIVA AMELIA GALLEGOS DÍAZ, RIOBAMBA 2018-2019. - Cabezas Jaramillo, Elizabeth Alexandra (2019)
In the Amelia Gallegos Díaz Educational Unit, there was evidence of a limited use of the games of initiation to quantity. Consequently, children showed little interest in learning mathematics. This background motivated the research, having the objective, to determine the influence of the games of initiation to the quantity in the development of the scope of mathematical, logical relation. The research is non-experimental, qualitative, and descriptive. It is based on inductive and deductive research because it allows knowing the scarce implementation of ludic activities in the logical-mathematical field. The observation was the instrument using ten indicators which allowed to obtain information of the 25 students of the primary first year. Concluding that the games of initiation to the amount are essential in the children because they are playful activities that help to improve the development of creativity and imagination, favoring in the development logical mathematical field relation.